Review of the Quality Assurance and Accreditation Policies and Practices in the Portuguese Higher Education: Self Evaluation Report - Santos, Sérgio Machado dos (2012)
1.1 The present review of the quality assurance and accreditation policies and practices in the Portuguese higher education was determined by a Ministerial decision of 21 November 2005 in the scope of a comprehensive international evaluation of the national higher education system. In this sense, the review does not fit strictly into the cyclical external reviews of ENQA’s member agencies foreseen in the Standards and Guidelines for Quality Assurance in the European Higher Education Area adopted at the Ministerial Summit in Bergen, since it was not an initiative from the higher education evaluation councils or from CNAVES, which are in a process of adaptation to the European standards and at the proper time could decide on the best way to be revised, under the general principles for the cyclical reviews proposed in the European Guidelines, namely in what concerns the subsidiarity principle. Also, in the present circumstances the review must go quite beyond an exercise of conformity with more or less routine procedures. Indeed, the Portuguese quality assurance system was developed under special circumstances, in a contractual way in which the initiative was mainly on the side of the higher education institutions. The evaluation process was first launched as a pilot-project of the Portuguese University Rectors’ Conference (CRUP), based on sound underlying principles with the core objective of contributing to the embedding of a quality culture inside the higher education institutions and, for this effect, to involve them strongly in a shared construction and development of the evaluation model. This philosophy was later adopted by a law approved by Parliament, which allowed for the institutions in each higher education sector to organise themselves to coordinate the internal evaluation process and to develop the external evaluation process under specified general requisites. In face of this innovative approach, quite unique in the Portuguese public administration, the most important exercise to carry out at the end of the just finished evaluation round is to analyse its impact on the higher education system, particularly within the institutions, to learn from the successes and from the difficulties in its implementation and to clarify the contractual model, defining more clearly the responsibilities of the political and academic powers. The leitmotif for the structural changes to be introduced in the evaluation system is not the conformity to the European standards, although of course they are important and must be met, but the improvement of the contractual model, keeping its basic principles while addressing its weakness, such as the need for clearer results, more tangible consequences and better information to the society. 1.2 The fact that the review by ENQA is somewhat untimely does not mean that CNAVES and the evaluation councils will not try to make the best of it and learn from the reflections to be made and from the experience and recommendations from the review panel. There was, therefore, a good mobilisation of the main actors which proved to be a great help in the preparation of this self-evaluation report. A Self-Evaluation Group was set up, including two elements from CNAVES (the coordinator of the Group, with the responsibility to draft the report and to act as liaison person with the review panel, and one student) and one element (and a substitute) from each of the four evaluation councils. However, all the executive bodies and secretariats have participated in the work and the report was thoroughly discussed in the evaluation councils and in CNAVES, where very valuable inputs were taken in. The composition of the Self-Evaluation Group with a brief biography of its members is indicated in Appendix 12.1.